2005
DOI: 10.1152/ajpregu.00165.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early gestation dexamethasone programs enhanced postnatal ovine coronary artery vascular reactivity

Abstract: .-Excessive exposure of the fetus to maternally derived corticosteroids has been linked to the development of adult-onset diseases. To determine if early gestation corticosteroid exposure alters subsequent coronary artery reactivity, we administered dexamethasone (0.28 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 ) to pregnant ewes at 27-28 days gestation (term being 145 days). Vascular responsiveness was assessed in endothelium-intact coronary and mesenteric arteries isolated from steroid-exposed and age-matched control fetal sheep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 31 publications
4
48
1
Order By: Relevance
“…Using this dex-exposure model, we have demonstrated that programmed sheep have coronary artery-specific increases in both superoxide production and angiotensin II (Ang II) responsiveness without alteration in Ang II receptor expression (6,7). Supporting the relevance of these findings, a role for renin-angiotensin system activation in programmed cardiovascular disease has now been demonstrated in studies that bridge animal models and experimental interventions (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Using this dex-exposure model, we have demonstrated that programmed sheep have coronary artery-specific increases in both superoxide production and angiotensin II (Ang II) responsiveness without alteration in Ang II receptor expression (6,7). Supporting the relevance of these findings, a role for renin-angiotensin system activation in programmed cardiovascular disease has now been demonstrated in studies that bridge animal models and experimental interventions (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 79%
“…Supporting the relevance of these findings, a role for renin-angiotensin system activation in programmed cardiovascular disease has now been demonstrated in studies that bridge animal models and experimental interventions (5,(7)(8)(9)(10)(11). Among its cardiovascular effects, Ang II is a prototypical agonist for vascular NADPH oxidase, an enzyme linked to progression of atherosclerotic plaques through increased endothelial superoxide production (12,13).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Evidence from animal models of fetal programming indicates that antenatal glucocorticoids have adverse cardiovascular effects in the adult offspring, with alterations in vascular reactivity being a common finding in animal models across several species. In sheep, antenatal exposure to dexamethasone at 27-28 dGA results in adult hypertension and alterations in mesenteric artery vascular reactivity in 123-126 dGA fetuses, and in coronary reactivity in 1-wk-old and 4-mo-old lambs (2,3). Repeated weekly exposure to low doses of dexamethasone starting at 103 dGA does not produce changes in blood pressure, but it does alter femoral artery sensitivity to ET-1 and to acetylcholine (ACh) in 5-mo-old lambs (4).…”
mentioning
confidence: 99%
“…Several contributing factors for the development of hypertension have been proposed, i.e. increases in cardiac output (9), in sodium retention (10,11), in sympathetic outflow (12), and altered vascular reactivity (2,3). ET-1 is the main endothelin generated in the endothelium and induces vasoconstriction, cell proliferation, and hypertrophy through the stimulation of smooth muscle ET A receptors and vasorelaxation through stimulation of endothelial ET B receptors (13).…”
mentioning
confidence: 99%